Analysis of Heteroplasmic Variants in the Cardiac Mitochondrial Genome of Individuals with Down Syndrome. Issue 1 (26th September 2016) - Hefti, Erik; Bard, Jonathan; Blanco, Javier G.
Abstract : In our article "Analysis of Heteroplasmic Variants in the Cardiac Mitochondrial Genome of Individuals with Down Syndrome", we used massively parallel sequencing to measure heteroplasmic variants in the cardiac mitochondrial DNA (mtDNA) from subjects with and without Down syndrome. We found the mitochondrial genomes in both groups to be similar in terms of the number, frequency and distribution of mtDNA variants. This research advances the understanding of tissular mtDNA variation in Down syndrome. ABSTRACT: Individuals with Down syndrome (DS, trisomy 21) exhibit a pro‐oxidative cellular environment as well as mitochondrial dysfunction. Increased oxidative stress may damage the mitochondrial DNA (mtDNA). The coexistence of mtDNA variants in a cell or tissue (i.e., heteroplasmy) may contribute to mitochondrial dysfunction. Given the evidence on mitochondrial dysfunction and the relatively high incidence of multiorganic disorders associated with DS, we hypothesized that cardiac tissue from subjects with DS may exhibit higher frequencies of mtDNA variants in comparison to cardiac tissue from donors without DS. This study documents the analysis of mtDNA variants in heart tissue samples from donors with ( n = 12) and without DS ( n = 33) using massively parallel sequencing. Contrary to the original hypothesis, the study's findings suggest that the cardiac mitochondrial genomes from individuals with and without DS exhibit many similarities in terms of (1) total number of mtDNA variants per sample, (2) the frequency of mtDNA variants, (3) the type of mtDNA variants, and (4) the patterns of distribution of mtDNA variants. In both groups of samples, the mtDNA control region showed significantly more heteroplasmic variants in comparison to the number of variants in protein‐ and RNA‐coding genes ( P < 1.00×10 −4, ANOVA).